Early intensification of therapy for type 2 diabetes mellitus and achievement of the target level of glycohemoglobin HbA1c are necessary factors to reduce the risk of micro- and macrovascular complications - M. S. Shamkhalova; O. Y. Sukhareva (Сахарный диабет)
Control of type 2 diabetes mellitus (T2DM) requires multifactorial behavioral and pharmacological treatment to prevent the development or slow the progression of complications. The main characteristics of T2DM — hyperglycemia and insulin resistance, combined with oxidative stress, low-level inflammation, epigenetic changes, genetic predisposition, activation of the renin-angiotensin-aldosterone system, causing endothelial dysfunction, are responsible for the metabolic environment that increases vascular risk in patients. Almost all patients with type 2 diabetes are at high and very high cardiovascular risk. The largest studies of the late XX-early XXI centuries. demonstrated a significant reduction in complications with intensive care early in the course of the disease and a «legacy effect» with the long-term historical value of HbA1c control during their observational follow-ups. The decrease in HbA1c may also play a role in mediating the positive effect on cardiovascular risk observed with the use of new hypoglycemic agents. The desire for glycemic control and the desire for organ-specific protection are not mutually exclusive, but complementary. Reassessing individual glycemic goals and achieving them at regular intervals with early intensification of therapy is key to overcoming clinical inertia.